Fakt i interpretacja w kontekście pytania o prawdę we współczesnym przekazie medialnym - Lisiecki, Marcin (Humaniora. Czasopismo Internetowe, 2022)
The article aims to analyze two concepts that are extremely important in the media, i.e. “fact” and “interpretation” and their relationship with “truth.” Addressing this issue results primarily from the frequent use of the colloquial understanding of these concepts and building, based on them, fragile theories regarding the correct message in the media. To organize the argument, the article is divided into two parts, which are devoted to – based on logical and philosophical research and methodology derived from historical sciences – the analysis of the concept of “fact,” and then “interpretation.” In addition, these considerations are supplemented with an attempt to show how we can relate to facts and carry out an interpretation to obtain the most adequate reality and communicable message.